Case Report: Administration of empirical antimicrobial therapy on an acute stroke patient with Suspected Hospital-Acquired Infection - Yuliawati; Iskandar, Mirna Marhami; Fitrianingsih; Kamariyah; Istarini, Attiya (Proceedings Academic Universitas Jambi, 2025)
Background: Principles of stroke management has established several aspects that can improve or worsen patient’s clinical neurological status and overall outcome. One of the factors that can significantly affect patient outcome is hospital-acquired infection (HAI). Objective: This case report aims to illustrate how a stroke patient seems to develop HAI, which hinders the progress of clinical improvement. Methods: A 53-year-old male patient presents with sudden onset of right-sided weakness and inability to speak five days ago. Patient is also somnolent, with dysphagia and global aphasia. Patient undergoes the workup for acute onset stroke, and the clinical, radiology and laboratory data is observed. Patient is diagnosed with left middle cerebral artery territory ischemia, with the risk faktor of hypercholesterolemia and stage 1 hypertension. Patient gradually gained full consciousness, can understand verbal commands, and can swallow soft foods. On the fourth day of inpatient stay, patient develops a fever. Additional tests are then ordered to investigate the suspected HAI, including inflammation and infection markers. Results: Patient showed elevated leukocyte levels specifically neutrophilia, elevated CRP, clear chest radiography. Hospital stay is lengthened for three more days on account of intravenous administration of empirical antibiotics, continued with oral antibiotics as blood culture results is awaited. No microbial growth was found on blood culture. Conclusion: This case highlights the challenges of administering empirical antimicrobial therapy on patients that show signs of inflammation caused by bacterial infection, which interferes with the main condition’s clinical progression. Several points may be taken into consideration to design a protocol that can manage such cases more efficiently and appropriately.